1996
DOI: 10.1021/jf9601731
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Water Vapor Permeability of Edible Films from Whey Protein Isolate andN-Ethylmaleimide or Cysteine

Abstract: The role of sulfhydryl/disulfide interchange in determining the water vapor permeability (WVP) and mechanical properties of edible films from whey protein isolate (WPI) was investigated. Nearly total inhibition of sulfhydryl/disulfide interchange by the sulfhydryl blocking agent N-ethylmaleimide (NEM) reduced protein solubility by 50%, but had no effect on WVP, Young's modulus, yield stress, or breaking stress. Breaking strain was reduced significantly at high levels of added NEM. Reduction of disulfide bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 17 publications
6
26
0
Order By: Relevance
“…However, our results support the hypothesis that hydrogen bonding plays a major role in the films mechanical properties. These results also corroborate those obtained by Fairly et al [30] who showed that the effects of hydrogen bonding far outweigh those of disulfide bonding in WPI films and that sulfhydryl/disulfide exchange does not significantly determine the films functional properties of, unlike their role in determining the strength of whey protein gels [31]. It should be noted that our values are comparable to those obtained with gelatin films, a biopolymer currently used in biomedical applications [4].…”
Section: Mechanical Propertiessupporting
confidence: 92%
“…However, our results support the hypothesis that hydrogen bonding plays a major role in the films mechanical properties. These results also corroborate those obtained by Fairly et al [30] who showed that the effects of hydrogen bonding far outweigh those of disulfide bonding in WPI films and that sulfhydryl/disulfide exchange does not significantly determine the films functional properties of, unlike their role in determining the strength of whey protein gels [31]. It should be noted that our values are comparable to those obtained with gelatin films, a biopolymer currently used in biomedical applications [4].…”
Section: Mechanical Propertiessupporting
confidence: 92%
“…The solubility was determined to be 38 ± 5% as shown in table 2. This relative insolubility in water is consistent with the observation that whey protein films are largely insoluble [20]. The high interaction density and the presence of intermolecular covalent bonds or physical knots could be responsible for part of the insolubility of these films.…”
Section: Thickness Density Moisture Content and Solubilitysupporting
confidence: 88%
“…In particular, unfolding of the native conformation of globular whey proteins at neutral pH leads to exposure of free sulfhydryl groups (SH) and hydrophobic amino acid side-chains, normally occluded within bovine serum albumin (BSA) and lg (Kazmierski & Corredig, 2003;Schmitt et al, 2009;Shimada & Cheftel, 1989). With further heat treatment, free SH may rapidly interchange with existing disulfide bonds to generate new inter-and intramolecular disulfide bonds that will engage toward protein aggregation (Fairley, Monahan, German, & Krochta, 1996;Schokker, Singh, Pinder, & Creamer, 2000). The formation of intermolecular disulfide bonds by sulfhydryldisulfide interchange is considered one of the major mechanisms of protein aggregation, and is mainly governed by formation of lg oligomers that combine into large aggregates (Havea, Singh & Creamer, 2002).…”
Section: Introductionmentioning
confidence: 99%